2002
DOI: 10.1143/jpsj.71.1052
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Mechanics of Image Restoration by the Plane Rotator Model

Abstract: On the basis of statistical mechanics formulation for problems of image restoration and errorcorrecting codes, we propose a new technique of image restoration for a binary image using the plane rotator model. In our formulation, the restored image is obtained from the equilibrium state of a ferromagnetic plane rotator model under a random field which consists of the corrupted image at finite temperature. The validity of our technique is evaluated by the dependence of overlap on the hyperparameters using the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…When the summation with respect to the intensity is first taken in Eqs. (7) to (9) and ρ(u) = ∑ x ρ(x, u) is taken into account, it turns out that ρ(u) has a four-body interaction for line variables u ij , which implies that the interaction between line fields is indirectly included by the model. In spite of this situation, the results in the numerical experiments in the present paper indicate that the RCMRF model has better performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the summation with respect to the intensity is first taken in Eqs. (7) to (9) and ρ(u) = ∑ x ρ(x, u) is taken into account, it turns out that ρ(u) has a four-body interaction for line variables u ij , which implies that the interaction between line fields is indirectly included by the model. In spite of this situation, the results in the numerical experiments in the present paper indicate that the RCMRF model has better performance.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is proposed to extend discrete states at each pixel to a continuous state in order to avoid local minima [5]. Saika and Nishimori [6,7] introduced a plane rotator model, as one © 2003 Wiley Periodicals, Inc.…”
Section: Introductionmentioning
confidence: 99%
“…Binary-valued Ising spin models, the q-state Potts model, and the continuous planar rotator are typical NGMRF examples. Widely studied in statistical physics, they have also found applications in areas such as image restoration [3][4][5] and spatial prediction [6].…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents a novel Gibbs Markov random field for spatial processes that take continuous values in a closed subset of the real numbers. The NGMRF is based on the parametric planar rotator spin model from statistical physics, which has successfully been applied to binary image restoration [36]. The spatial prediction method proposed herein was prompted by our recent study which revealed that a suitably modified planar rotator model changes its low-temperature quasi-critical behavior (which is characterized by power-law decaying correlation function) to a regime characterized by a flexible short-range spatial correlation function [37].…”
Section: Introductionmentioning
confidence: 99%